Osobní zájmena ve fino-sámských jazycích v uralské perspektivě - Hofírková, Lucie; Blažek; Václav (2013)
In the article the personal pronouns of all Uralic languages are collected and summarized from the point of view of their declension. Personal pronouns of Balto-Finnic and Saamic languages are collected and analyzed on the basis of their internal structure and external comparison with all other branches of Uralic languages. Applying the methods of internal reconstruction, finally the minimal paradigm was reconstructed.